Hubungan Antara Hafalan Al-Qur’an Dengan Hasil Belajar Bahasa Arab Siswa Kelas VIII Program Takhassus - Ahmad Hadi Setiawan; Masfiyatul Asriyah (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2022)
Arabic is a tool used by humans to communicate. Arabic is very important to learn for every Muslim considering the Qur'an and hadith which are the source of Islamic religious law in Arabic. Darul Fattah Qur'an Middle School is one of the schools that makes Arabic a compulsory subject for every student. The purpose of this study was to determine the relationship between the memorization of the Qur'an and the Arabic learning outcomes of eighth grade students of the Takhassus program at Darul Fattah Middle School Qur'an Bandar Lampung. This study uses a quantitative approach using a correlation design. This research was carried out at Darul Fattah Qur'an Middle School in Bandar Lampung. The sample of this study was 15 students from class VIII of the Takhassus program which were determined using purposive sampling technique. The instrument consists of interviews and documentation. The data analysis technique uses the Product Moment correlation analysis technique. Based on the calculation of the correlation coefficient with a significance level of 5% and 1% with r count > r table or 0.644 > 0.514/0.641, thus Ha is accepted. This means that there is a positive relationship between the memorization of the Qur'an and the Arabic learning outcomes of 0.644. The level of the relationship between the memorization of the Qur'an and the learning outcomes of Arabic students of class VIII of the takhassus program of SMP Qur'an Darul Fattah Bandar Lampung is included in medium category.